The Impact of Cultural Schemata on EFL Reading Comprehension: The Case of First-Year Moroccan University Students - EL KOUAR, Brahim; Hdii, Saida (International Journal of Language and Literary Studies, 2025)
The prime objective of the study was to investigate the effects of background knowledge on reading comprehension among Moroccan EFL learners at the tertiary level. The hypothesis tested was that the experimental group would perform better than the control group on the grounds of providing cultural background knowledge prior to reading. To meet this objective, the study made use of two types of instruments: a test comprising structured test items and a post-reading feedback questionnaire. A cohort of sixty-eight university students took part in the study. The participants were divided into two groups: the control group and the experimental group. The study adopts a mixed-method experimental design to triangulate data on both the effect of background knowledge and students’ perceptions of the intervention on EFL learners' reading comprehension. The results show that the experimental group performed better than the control group on the basis of providing cultural background knowledge. The major pedagogical implication of the study is that pre-reading activities, in general, and providing background knowledge, in particular, are useful instructional tools for teachers in the EFL context to facilitate students' reading comprehension at the tertiary level.